Contribución al conocimiento de la morfología y distribución en Chile de Entomoneis paludosa (W. Smith) Reimer (Bacillariophyta) - Rivera, Patricio (Gayana Botánica, 2020)
In this study, the diatom Entomoneis paludosa (W. Smith) Reimer is reported for the first time from Salar de Ascotán, in the Región of Antofagasta, Chile. Only isolated valves were found, and the species is described using light and electron microscopy techniques. Comments about its morphology and ecology are also given. Till now E. paludosa had been reported only from other four Chilean localities.